EFFECT OF NIGELLA SATIVA ON NUMBER OF CYSTIC FOLLICLES IN LETROZOLE INDUCED POLYCYSTIC OVARIES IN MICE - Noreen Anwar; Shabnam Hamid; Shadab Ahmed Butt (Pakistan Armed Forces Medical Journal, 2016)
Objective: To observe the protective effect of Nigella sativa on number of cystic follicles in Letrozole induced polycystic ovaries in mice. Study Design: Laboratory based randomized control trial. Place and Duration of Study: Department of Anatomy, Army Medical College in collaboration with National Institute of Health from Nov 2014 to Nov 2015. Material and Methods: Forty female BALB/c mice were selected and divided in four groups, each having 10 animals. Group A served as control and was given normal diet. Group B was given Letrozole at a dose of 1milligram/kilogram body weight. Group C was treated with Letrozole for eight weeks at a dose of 1milligram/kilogram body weight and Nigella sativa seeds powder at a dose of 10grams/kilogram body weight once daily starting at 22 day and continued up to eight weeks. Group D was treated with Letrozole for eight weeks at a dose of 1milligram/kilogram body weight and Nigella sativa oil at a dose of 4milliliter/kilogram body weight once daily starting at 22 day and continued up to eight weeks. Animals were dissected a day after last dose. Size, shape, color and consistency of ovary was observed. Right ovary was processed, embedded and stained for histological study. Number of cystic follicles were counted and noted. Results: Significant number of cystic follicles was observed in ovaries of animals of group B as compared to group A. While their number decreased significantly in group C and D as compared to group B. Conclusion: Nigella sativa seeds powder and its oil, both have a similar protective effect on histomorphology of ovary of polycystic ovarian syndrome (PCOS) in mice by decreasing the number of cystic follicles.